Development of life values in future bachelors during the period of study in higher education institutions - Khavina, Irina; Chebakova, Yuliia (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article focuses on the development of future bachelors’ life values during the period of study in higher education institutions. The theoretical and methodological analysis of the definition of “life values” is carried out. The issue of formation of the concept of students’ life values is considered. Various classifications of the development of students’ life values are substantiated. The study of the state of development of future bachelors’ life values during the period of study in a higher education institution is carried out. Recommendations for the further development of life values of both future bachelors and specialists are given.

У статті приділено увагу розвитку життєвих цінностей у майбутніх бакалаврів протягом періоду навчання у закладах вищої освіти. Проведено теоретико-методологічний аналіз дефініції “життєві цінності”. Розглянуто питання становлення поняття життєві цінності у студентів. Обґрунтовані різні класифікації розвитку життєвих цінностей у студентів. Проведено дослідження стану розвитку життєвих цінностей у майбутніх бакалаврів протягом періоду навчання у закладі вищої освіти. Надані рекомендації, щодо подальшого розвитку життєвих цінностей як у майбутніх бакалаврів, так й фахівців.
Розвиток життєвих цінностей у майбутніх бакалаврів протягом періоду навчання у ЗВО
Keywords: life values; future bachelors; students; period of study; higher education institution; життєві цінності; майбутні бакалаври; студенти; період навчання; заклад вищої освіти